Treatment of Multiple Sclerosis. Issue 4 (August 2022) - Cross, Anne; Riley, Claire
ABSTRACT: PURPOSE OF REVIEW: Given the expansion of options for the treatment of relapsing multiple sclerosis, this review outlines the framework for developing a treatment strategy, with consideration of when to switch or discontinue therapies, and a comprehensive elaboration of the mechanisms of action, efficacy, and safety considerations for each of the therapeutic classes. RECENT FINDINGS: The armamentarium of immunotherapies has grown rapidly, to encompass 19 US Food and Drug Administration (FDA)-approved immunotherapies available in 2021, which are addressed in the review. The coronavirus pandemic that began in 2020 underscored existing concerns regarding vaccine efficacy in those treated with immune-suppressing immunotherapies, which are also addressed here. SUMMARY: By choosing a treatment strategy before exploring the individual medications, patients and providers can focus their efforts on a subset of the therapeutic options. Although the mechanisms of action, routes of administration, efficacy, safety, and tolerability of the described agents and classes differ, all are effective in reducing relapse frequency in multiple sclerosis (MS), with most also showing a reduction in the accumulation of neurologic disability. These powerful effects are improving the lives of people with MS. Pharmacovigilance is critical for the safe use of these immune-modulating and -suppressing agents, and vaccine efficacy may be reduced by those with immune-suppressing effects.